ENHANCING LEGAL ENGLISH PROFICIENCY: STRATEGIES FOR LAW STUDENTS - Sur’atovna, Nohida Mukhtorova (International Journal Multidisciplinary (IJMI), 2025)
Objective: The primary objective of this article is to identify and discuss effective strategies for enhancing legal English proficiency among law students. Additionally, the article evaluates the importance of integrating cultural competence into legal English education to foster better understanding and communication in diverse legal environments. As globalization continues to shape the legal profession, the ability to communicate effectively in English has become paramount for law students. Method: The methods proposed aim to improve reading, writing, speaking, and listening skills within a legal context, thus preparing students for the demands of the global legal profession. This article explores various strategies to enhance legal English proficiency among law students, focusing on practical methods that incorporate reading, writing, speaking, and listening skills. Results: By implementing these strategies, law students can improve their legal vocabulary, comprehension, and overall communication skills, which are essential for success in the legal field. Novelty: This article highlights the integration of cultural competence into legal English education, an approach that is often overlooked in traditional language instruction. It also emphasizes practical, skill-based methods tailored specifically to the legal context, offering a more targeted framework for preparing law students for global legal communication.